Open fractures with soft-tissue loss: Coverage options and timing of surgery. Issue 1 (March 2020) - Coles, Chad P.
Abstract : Abstract: Open fractures with soft-tissue loss remain challenging injuries to treat. These often high-energy fractures are at a higher risk of delayed healing and at much higher risk of infection than open fractures with less significant soft-tissue injury. The initial management of the open wound, flap coverage options, and the timing of definitive coverage all remain areas of controversy, which will be discussed in this article.